2019
DOI: 10.3329/bjms.v18i3.41613
|View full text |Cite
|
Sign up to set email alerts
|

Human Leukocyte Antigen Genetic Variations in Obstructive Sleep Apnea Patients that were positive for HLA-DQB1*0602.

Abstract: Background: Genetic variations in the HLA system may cause susceptibility to a large number of autoimmune and infectious diseases, and the complexity of HLA makes it hard to investigate HLA types associated with diseases. The association between HLA and Obstructive Sleep Apnea (OSA) is not well investigated due to the complexity of OSA pathogenesis; including genetic and non-genetic in different populations. Our previous study using PCR-SSPs technique showed that HLA-DQB1*0602 allele is associated with almost … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…Overallfindingsindicate that undergraduate education module and clinical experiences should be developed and improved to help the identification and management of patients with OSA. In order to improve OSA knowledge and its awareness, it has been suggested that sleep disorder,particularly OSA, should be incorporated into the new dental academic curriculum.Not only theoretically, dental students should also be exposed and experienced themselves on how to recognise clinical features, assess the risk factor, genetic predisposition 30 ,andmanagementof OSA patients with correct oral appliances as well as referral to specialists.…”
Section: Discussionmentioning
confidence: 99%
“…Overallfindingsindicate that undergraduate education module and clinical experiences should be developed and improved to help the identification and management of patients with OSA. In order to improve OSA knowledge and its awareness, it has been suggested that sleep disorder,particularly OSA, should be incorporated into the new dental academic curriculum.Not only theoretically, dental students should also be exposed and experienced themselves on how to recognise clinical features, assess the risk factor, genetic predisposition 30 ,andmanagementof OSA patients with correct oral appliances as well as referral to specialists.…”
Section: Discussionmentioning
confidence: 99%